International Conference on the Epidemiology and Control of Biological, Chemical and Physical Hazards in Pigs and Pork 2007
DOI: 10.31274/safepork-180809-54
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica serovar Typhimurium isolates associated with septicaemia in swine

Abstract: In th1s study we characterized, usmg genotyping and phenotypmg methods, ISolates {n=33) from septicaemia outbreaks in swine herds as well as isolates {n=33) recovered from healthy ammals at slaughter. We determined the antimicrobial agents resistance profiles using 24 different an timicrobial agents by the d1sk d1ffus1on on agar method, the phage type, the plasmid profiles and the PFGE profiles usmg Xbal and Spel as restriction enzymes for each isolates. Resistance to as much as 10 antimicrobial agents was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…A diarreia neonatal de bezerros acarreta graves prejuízos à pecuária tanto pela mortalidade quanto pelos custos envolvidos com o tratamento e atraso no crescimento dos animais, sendo a salmonelose uma das causas mais importantes, com destaque para Salmonella (S.) enterica subespécie enterica sorotipos Typhimurium e Dublin (Fecteau et al, 2003). A principal porta de entrada para a ocorrência da infecção é a cavidade oral, pela ingestão de água e alimentos contaminados.…”
unclassified
See 2 more Smart Citations
“…A diarreia neonatal de bezerros acarreta graves prejuízos à pecuária tanto pela mortalidade quanto pelos custos envolvidos com o tratamento e atraso no crescimento dos animais, sendo a salmonelose uma das causas mais importantes, com destaque para Salmonella (S.) enterica subespécie enterica sorotipos Typhimurium e Dublin (Fecteau et al, 2003). A principal porta de entrada para a ocorrência da infecção é a cavidade oral, pela ingestão de água e alimentos contaminados.…”
unclassified
“…A infecção resulta em ampla variedade de sinais clínicos, em função da idade do animal e do sorotipo envolvido, sendo necessárias doses de 10 9 e 10 10 unidades formadoras de colônia (UFC) de S. Typhimurium para provocar a doença em bovinos sadios (Santos et al, 2002). Em bezerros com até oito semanas de idade, a infecção pode causar diarreia aguda, aquosa e fétida, desidratação, desequilíbrio eletrolítico, endotoxemia, bacteremia e morte (Fecteau et al, 2003), sendo a taxa de mortalidade inversamente proporcional à idade (Santos et al, 2002).  Os objetivos do presente estudo foram avaliar o quadro clínico de bezerros submetidos à infecção experimental com 10 9 UFC de S. Typhimurium e verificar a viabilidade do modelo experimental na indução da doença em bezerros.…”
unclassified
See 1 more Smart Citation
“…In comparison, Lukinmaa et al (2006) found that 96% of multiresistant DT104 strains studied belonged to one particular PFGE type. Interestingly, results from a study by Bergeron et al (2007) suggest a greater genetic diversity of Salmonella Typhimurium DT104 in North America than that in Europe. Despite the limitations of PFGE analysis in the current study, it is an invaluable tool for the epidemiological typing of Salmonella serovars; however, it may be inaccurate to draw epidemiological conclusions based on a single fingerprinting method (Liebana et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…This status establishes the maintenance of the infection in the involved farms, causing eminent economic losses for intensive livestock farming, and represents an important public health risk [4]. Swine represent reservoir for human infections [5]. In fact according to scientific report of EFSA the prevalence of Salmonella-positive slaughter pigs was up to 10.3%, although with variation among Member States, including both primary infections and surface contamination of carcasses.…”
Section: Introductionmentioning
confidence: 99%